New Testament miracle stories in Ghanaian mother-tongues: case studies and their hermeneutical implications - Boateng, Abraham (Studies of the Bible and Its Reception (SBR), 2024)
"This book examines the translations of selected miracle stories from the Hebrew Bible, Septuagint (LXX) and the Greek New Testament into selected Ghanaian mother-tongues, considering possible shifts of meaning that occur in translating. 1Kings 18:25-38, Mark 9:14-29 and Luke 7:11-17 are used as case studies. The author draws out semiotic-hermeneutical nuances of these texts as they are understood in the Ghanaian context and addresses questions in the field of Biblical studies concerning the relevance of intercultural hermeneutics for current trends in Ghanaian Christianity. Particularly important is the high premium placed on 'miracles' in present-day Ghanaian spirituality, making a careful analysis of these stories particularly relevant for the Ghanaian audience. The study also explores several factors that influence the translation process and have a bearing on the reception and use of the text. It follows the growing calls for a shift in African Biblical hermeneutics from the theological heritage of Europe and America to the emerging theological trajectories of Africa. This post-colonial shift re-examines the translated text, moving from what the text might have meant to what the text might mean in Africa."--